Non-Invasive Glucose Monitoring Technologies Innovations Applications and Future Directions - Wu Kerui (MATEC Web of Conferences)
Diabetes mellitus has emerged as a major chronic disease threatening global health. While traditional glucometers enable point-of- care testing, their invasive nature induces patient resistance that significantly compromises disease management efficacy. Contemporary non-invasive technologies have achieved breakthrough progress, yet critical research gaps persist in multi-physics coupling mechanisms and personalized calibration model development. This comprehensive review analyzes principle innovations and industrial applications of non-invasive glucose monitoring technologies, employing technical evolution pathway analysis and clinical data benchmarking to evaluate seven methodological paradigms - including spectroscopy, electrochemistry, and microwave sensing - along with their translational achievements in wearable devices and healthcare systems. Key findings demonstrate: multi-modal sensing reduces detection errors to 8.7% through signal complementarity, with millimeter-wave radar technology achieving 5-minute continuous monitoring (r=0.912); flexible electronic skin breakthroughs 72-hour operational endurance (sensitivity 0.03nA/(mg/dL)); and intelligent closed-loop systems enhance glycated hemoglobin compliance rates by 42%. Current technical bottlenecks manifest as individual calibration variation coefficients exceeding 12% and blood-interstitial fluid glucose lag (8-15 minutes), with emerging solutions trending toward deep learning-based dynamic compensation models (83% error correction) and terahertz quantum cascade detection (0.1mmol/L detection limit).